2012
DOI: 10.1016/j.atherosclerosis.2011.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy stimulates the formation of initial atherosclerotic lesions: Reversal by adrenal transplantation

Abstract: Long-term changes in the secretion of immunosuppressive adrenal-derived glucocorticoid hormones influence cardiovascular disease risk. Here we determined the consequences of changes in adrenal steroid metabolism for the development of atherosclerotic lesions in mice. Atherosclerosis-susceptible low-density-lipoprotein (LDL) receptor knockout mice were subjected to adrenalectomy (ADX) or a control (SHAM) operation and subsequently fed an atherogenic diet for 4 weeks. Atherogenic diet feeding raised plasma corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…In contrast to the change in hepatic glucocorticoid action in LCAT KO mice, leukocyte-specifi c glucocorticoid signaling is apparently normal in these mice because the susceptibility to endotoxemia is unaffected. Such a difference in cell-specifi c glucocorticoid sensitivity (i.e., high glucocorticoid receptor sensitivity in leukocytes and low glucocorticoid receptor sensitivity in hepatocytes) has also been detected in our previous adrenalectomy and adrenal transplantation studies ( 30 ).…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to the change in hepatic glucocorticoid action in LCAT KO mice, leukocyte-specifi c glucocorticoid signaling is apparently normal in these mice because the susceptibility to endotoxemia is unaffected. Such a difference in cell-specifi c glucocorticoid sensitivity (i.e., high glucocorticoid receptor sensitivity in leukocytes and low glucocorticoid receptor sensitivity in hepatocytes) has also been detected in our previous adrenalectomy and adrenal transplantation studies ( 30 ).…”
Section: Discussionsupporting
confidence: 74%
“…We recently observed that feeding mice a cholic acid-containing atherogenic diet for 4 weeks induced a sustained increase in plasma corticosterone levels (van der Sluis et al, 2012). Importantly, in the current study, we now also show that short-term treatment with the synthetic FXR agonist GW4064 induces an acute 45% increase in the plasma level of corticosterone.…”
Section: Discussionsupporting
confidence: 64%
“…Adrenaltransplanted C57BL/6 were fed an atherogenic semisynthetic cholic acid-containing high cholesterol/high fat diet (15% (wt/wt) cacao butter, 1% (wt/wt) cholesterol, and 0.5% (wt/wt) cholic acid; Hope Farms, Woerden, NL) for 10 weeks starting from 6 weeks after the adrenal transplantation to stimulate the general steroidogenic activity of the adrenals. 23 On the basis of visual examination of the residual amount present at the time of cage changes, no major difference in the average food intake was noted between the 2 experimental groups while feeding the atherogenic diet. At the end of the study, 16 weeks postadrenal transplantation, mice were fasted overnight, anesthetized, and euthanized.…”
Section: Arterioscler Thromb Vasc Biolmentioning
confidence: 93%